Nation and Nationality: Africa in the Fiction of Doris Lessing - Akhter, Tawhida (International Journal of Psychosocial Rehabilitation, 2020)
The present work throws light on the mindset of the characters particularly with philosophical, psychological and social insights. This article explores the psychological elements in the Short Story collection African Stories of Doris Lessing. Lessing is a well renowned and Nobel laureate writer in English. Her short stories are remarkable for portraying the stark reality. The themes of Subjugation, Alienation and search for identity and realisation of self are present in this collection. This research work explores the psychological agony faced by the characters and how the anxieties actually bring about self-development. It also highlights that human emotions, relationships and situations are the essence of human existence. Her short stories have a positive impact on their readers and grow psychologically strong; the characters have the capacity to wrestle with the existential concerns and uplift humanity and improve their conditions.